Development and validation of a dissolution test for lodenafil carbonate based on in vivo data. (24th April 2013) - Codevilla, Cristiane Franco; Castilhos, Tamara dos Santos; Cirne, Carolina Araújo; Froehlich, Pedro Eduardo; Bergold, Ana Maria
Abstract: Introduction : Lodenafil carbonate is a phosphodiesterase type 5 inhibitor used for the treatment of erectile dysfunction. Currently, there is no dissolution test reported for lodenafil carbonate and this drug is not listed in any pharmacopoeia. Objective : The present study focused on the development and validation of a dissolution test for lodenafil carbonate tablets, using a simulated absorption profile based on in vivo data. Methods : The appropriate conditions were determined after testing sink conditions. Different conditions as medium, surfactant concentration and rotation speed were evaluated. The percentage of dose absorbed was calculated by deconvolution, using the Wagner–Nelson method. Results : According to the obtained results, the use of 0.1 M HCl + 1.5% SLS (900 mL, at 37 + 0.5 °C) as the dissolution medium, paddles at 25 rpm were considered adequate. The samples were quantified by UV spectroscopy at 295 nm and the validation was performed according to international guidelines. The method showed specificity, linearity, accuracy and precision, within the acceptable range. Kinetics of drug release was better described by the first-order model. Conclusion : The proposed dissolution test can be used for the routine quality control of lodenafil carbonate in tablets.